Medicine misuse: A systematic review and proposed hierarchical terminology. Issue 4 (8th December 2020) - Singier, Allison; Noize, Pernelle; Berdaï, Driss; Daveluy, Amélie; Arnaud, Mickaël; Molimard, Mathieu; Bégaud, Bernard; Salvo, Francesco
Abstract : Aims: Although medicine misuse is a public health issue, it has multiple meanings in the medical literature. This study aimed to characterize, classify and identify the most appropriate definitions of medicine misuse. Methods: A systematic review was performed in Medline, ISI Web of Science, SocINDEX, PsycInfo, PsycArticles and Psychological and Behavioral Sciences Collection, using keywords related to "misuse", "appropriateness" and "medicine" between 1 November 2008 and 25 August 2020. Additional searches were conducted in websites of regulatory agencies and public health institutions. Two authors independently selected studies providing both definitions and examples of misuse, while a third resolved disagreements. Definitions were used to propose a hierarchical classification based on initiator, intent, purpose and context of medicine misuse. The study is registered on PROSPERO: CRD42018115789. Results: Of 3404 identified records, 51 were included. A total of 71 definitions and 74 examples of misuse were retrieved. When the prescriber is initiator and according to intent, potential medicine misuse referred to "intentional or unintentional prescribing not in line with clinical evidence". Based on context, they could prescribe medicines not clinically justified, i.e. overprescribing, or prescribe indicated medicines incorrectly, i.e. misprescribing. Among other groups of definitions, those overlapping with drug abuse or medication use errors were considered out‐of‐scope. Conclusion: This systematic review provides a comprehensive overview of the terms and definitions used to characterize medicine misuse and could serve as a basis for a terminology that makes clear distinctions between misuse, abuse and errors . Abstract :